REVITALISASI MAHKOTA CENDERAWASIH PAPUA SEBAGAI WUJUD KEARIFAN LOKAL DI JEMAAT GKI KASIH PERUMNAS, KOTA SORONG, PROVINSI PAPUA BARAT DAYA - Palyama, Folce Elden; Leuwol, Natasya Virginia; Suripatty, Roberthair; Palinggiran, Serniati Lisma; Rumbekwan, Helena Grace; Kambu, Febelina (Universitas Mataram, 2025)
The Papua Cendrawasih crown is a type of handicraft that was originally made from the feathers of living birds of paradise. The Papuan Bird of Paradise Crown has high cultural and aesthetic value, a symbol of natural beauty and is the identity of the Papuan people. Efforts to revitalize, preserve, and maintain a balance between appreciation of Papuan culture and protection of the existence of birds of paradise require strict policies and supervision to ensure that the making of the Papuan bird of paradise crown does not endanger the survival of the birds of paradise which are currently almost extinct and do not violate the laws governing the protection of wildlife. The main objective of the program, through the Revitalization of the Papuan Bird of Paradise Crown as a form of local wisdom at GKI Kasih Perumnas, is that young people have the ability to receive cultural traditions so that they do not become extinct, so that they are in demand again, by being processed into valuable and useful things. The methods used are First, socialization and Focus Group Discussion (FGD). Second, the training method for making Papuan bird of paradise crowns by imitation. Third, measuring the level of understanding of participants at the beginning and end of the activity, through the Pre-Test and Post-Test. The results obtained from this activity are, seen from the results of the higher post-test scores, namely 90% of youth participants mastered the material and stages of making Papuan bird of paradise crowns by imitation, compared to the pre-test conducted before the training where only 10% of youth already knew it. Youth are able to create jobs, increase economic income, encourage innovation and the development of local wisdom potential in the community, as well as revive, maintain traditions and cultures so that they do not become extinct, in the city of Sorong, Southwest Papua Province.